2013
DOI: 10.1111/j.1582-4934.2012.01656.x
|View full text |Cite
|
Sign up to set email alerts
|

A role for two‐pore potassium (K2P) channels in endometrial epithelial function

Abstract: The human endometrial epithelium is pivotal to menstrual cycle progression, implantation and early pregnancy. Endometrial function is directly regulated by local factors that include pH, oxygen tension and ion concentrations to generate an environment conducive to fertilization. A superfamily of potassium channels characterized by two-pore domains (K2P) and encoded by KCNK genes is implicated in the control of the cell resting membrane potential through the generation of leak currents and modulation by various… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 54 publications
2
11
0
Order By: Relevance
“…Studies have proposed that this might occur through regulation of the membrane potential [54]. In apparent contrast to some studies [55][58] but in agreement with others [59], [60], we found that hyperpolarization caused by mutations in a K + channel can lead to tissue overgrowth. Although we observed a hyperpolarizing effect of the alf mutation in Xenopus oocytes, we cannot exclude that this, in turn, triggers a depolarization, either at cellular level or in the surrounding tissues during development of the fin.…”
Section: Discussionsupporting
confidence: 90%
“…Studies have proposed that this might occur through regulation of the membrane potential [54]. In apparent contrast to some studies [55][58] but in agreement with others [59], [60], we found that hyperpolarization caused by mutations in a K + channel can lead to tissue overgrowth. Although we observed a hyperpolarizing effect of the alf mutation in Xenopus oocytes, we cannot exclude that this, in turn, triggers a depolarization, either at cellular level or in the surrounding tissues during development of the fin.…”
Section: Discussionsupporting
confidence: 90%
“…K ϩ current efflux and anion inflow help maintain cell electroneutrality during the apoptotic volume decrease process (9). Tetraethylammonium (TEA) is a non-selective KChs inhibitor that has been extensively used as a molecular probe to study their structure (10) and characteristics of the regulation pathways (11,12). A four-peptide sequence containing Phe or Tyr residue on the loop surface of KCh proteins is a recognition region for TEA, and it is very conservative (13).…”
mentioning
confidence: 99%
“…Although many studies have suggested that inhibiting TREK-1 expression might promote cell proliferation, some authors have reported different results [14,42] . Specifically, it has been reported that TREK-1 is highly expressed in prostate cancer cells but not in normal prostatic tissues [14] .…”
Section: Discussionmentioning
confidence: 99%